2016
DOI: 10.2174/1871520615666150511094201
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Regulates Angiogenic Factors under Hypoxia in Breast Cancer Cell Lines

Abstract: Angiogenesis is the process of new blood vessel formation, regulated by a number of pro- and antiangiogenic factors and usually begins in response to hypoxia. Exogenous administration of melatonin has shown numerous anti-tumor effects and appears to inhibit tumor angiogenesis. However, many factors involved in the anti-angiogenic effect of melatonin are still under investigation. Here, we evaluate the effects of melatonin on cell viability and expression of angiogenic factors in MCF-7 and MDA-MB-231 breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 75 publications
7
37
0
Order By: Relevance
“…Consistent with our results, a recent study demonstrated that melatonin reduced the expression of VEGFR2 in breast cancer cells (MCF-7 and MDA-MB-231 cell lines), and also in mammary tumors of athymic nude mice [27,52]. …”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, a recent study demonstrated that melatonin reduced the expression of VEGFR2 in breast cancer cells (MCF-7 and MDA-MB-231 cell lines), and also in mammary tumors of athymic nude mice [27,52]. …”
Section: Discussionsupporting
confidence: 92%
“…Early studies reported that melatonin produced antiproliferative effect in breast cancer cells in vitro [47], and inhibited the growth of mammary tumors in rats [48, 49]. Afterwards, different mechanisms of melatonin's anticancer effects were identified successively, such as inducing apoptosis [50], antiestrogenic effect through ERα-signaling pathway and inhibiting aromatase activity [51–53], modulation of melatonin receptors [54], and inhibition on invasion [55] and angiogenesis [56]. …”
Section: Experimental Studiesmentioning
confidence: 99%
“…For breast cancer, 1 nM melatonin reduced the viability of hypoxic MCF-7 and MDA-MB-231 human breast cancer cells and decreased both gene and protein expression of HIF-1α and VEGF-A ( p < 0 .05), indicating an anti-angiogenesis effect [56]. Additionally, Alvarez-Garcia et al .…”
Section: Experimental Studiesmentioning
confidence: 99%
“…However, the mechanisms of melatonin's antiangiogenic in any tumor including NSCLC are still unclear. Numerous studies have documented that melatonin exhibits antiangiogenic actions, in part, by downregulating VEGF and HIF-1α in several cancers via different mechanisms; the cancer types included breast [16, 149], prostate [150152], colon [153, 154], liver [155], and pancreatic cancer [156, 157]. These studies may provide reference for the future work in the NSCLC research field.…”
Section: Potential Directionsmentioning
confidence: 99%